Employer's rights and contractor's liabilities in relation to construction defects after final certificate - Tan, Pei Ling (2007)
Most of the standard forms of contract contain provisions dealing with defective works. Defective works could be in the forms of design fault, defective building materials or bad workmanships. Any defects, shrinkages or other faults arising during construction and defects liability period due to defective materials or workmanship must be put right by the contractor at his own expense. The contract administrator will usually mark the end of the defects liability period with the issue of a further certificate, known as a Certificate of Making Good Defect. Subsequently, final certificate will be issued to the contractor stating amount finally due to him. Generally, final certificate will discharge the contractor’s liability for the defective works and the cost for remedying them. Employers will need to be wary as they can preclude the employer from claiming damages from the contractors for defects which appear after the issue of the final certificate. However, court will generally not regard a certificate as being final except where very clear words are used in the contract. This research intends to identify the legal position of the construction contract parties in relation to their rights and liabilities in defects after the issuance of Final Certificate. This research was carried out mainly through documentary analysis of law journals and law reports. Result shows that there are four circumstances to be considered when determining the liability of defects after final certificate, namely by referring to the conclusiveness evidence, consequential damages/loss, patent defects and fraud/concealment.